ANALISIS PENGARUH PDRB PERKAPITA, IPM, KEMISKINAN DAN PENGANGGURAN TERHADAP MIGRASI TENAGA KERJA KE LUAR NEGERI - Moh Faizin (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2020)
Problems related to employment are a problem that often occurs in developing countries such as Indonesia. Placement of migrant workers abroad, in addition to contributing about the country often also provide assistance in the community specifically for migrant workers themselves. This study aims to analyze the factors that increase the workforce abroad. By using panel regression data analysis conducted in several districts in East Java for the period 2011-2018. GRDP variable per capita against TKI variables, while for other variables not. The fourth variable also shows a simultaneous and significant effect on the TKI variable.